The relationship of atmosphere, satisfaction, and loyalty: Sample of a fitness center - Mehmet Oztas; Ali Sevılmıs; Erkan Faruk Sırın (Türk Spor ve Egzersiz Dergisi)
In the recent years, that fitness market rapidly grows, understanding of its importance and change of suggestions according to demand also revealed the importance of intangible elements as well as tangible elements. The aim of this study is to measure the relationship of atmosphere, satisfaction, and loyalty the customers, who are member to a private fitness center, perceive from this center. The study group consists of 503 participants (nmale = 465; nfemale = 38), who are at least for six month to a private fitness center, with convenience sampling method. In this study, “Personal Information Form”, “Perceived Leisure Time Loyalty and Leisure Time Satisfaction Scale”, and "Fitness Center Atmosphere Scale" were utilized. In the analysis of data, correlation and regression analysis was used for examining the relationships between the variables and explanatory factor analysis for fitness center scale. As a result of the analyses, it was identified that fitness center atmosphere affected customer satisfaction and, satisfaction, customer loyalty. This study can cause the importance of atmosphere in the behaviors of customer satisfaction and loyalty to be better understood.